Measuring Technical and Vocational Education and Training (TVET) Teacher’s Technical Competency and the Development of Programme-Specific-Directory - Minghat, Asnul Dahar; Mustakim, Siti Salina; A, Ana.; G.K , Kassymova; Suparman (International Journal of Psychosocial Rehabilitation, 2020)
Relevant competencies among Technical and Vocational Education and Training (TVET) instructors is important in the current development of education that necessitates the pedagogical skills and knowledge is the real world. The primary aim of this study is to (1) determine the relationship between Teaching Method (TM), Curriculum Module (CM), Learner’s Knowledge (LK) with Pedagogical Skills and Knowledge (PSK), and (2) identify the mean differences of Teaching Method, Curriculum Module, and Learner’s Knowledge with race, gender, age, industry involvement, instructor’s highest academic, and types of position. Data is collected from a survey to 106 instructors from eight Technical Institutions. Findings analysed using SPSS v21 indicated that there is significant difference between TM with PSK (r=0.595, p<0.01), CM with PSK (r=0.435, p<0.01), and LK with PSK (r=0.373, p<0.01). It is highlighted from ANOVA findings that there is a mean difference significant (0.021) between PSK with gender, no mean difference significant (0.0180) between PSK with age, no mean difference significant (0.522) between PSK with industry involvement, and no mean difference significant (0.979) between PSK with instructor’s highest academic (p>0.05). This study contributes towards the development of Programme-Specific-Directory amongst TVET instructors to be utilized in aligning constructively the schedule of curriculum in their particular technical institutions.